Differences in pacing during a 100km ultra-trail marathon between TOP-10 and NOT TOP-10 finishers - de Waal, S.; Jacobs, S.; Lamberts, R. (29th Annual Congress of the European College of Sport Science, 2-5 July 2024, Book of Abstracts, 2024)
INTRODUCTION: Pacing strategies during endurance efforts are learned behaviours which vary depending on athlete experience, race length, and terrain [1]. Previously, optimal ultra-trail marathon running pacing strategies have been described as `steadier` [2] or by `limiting` fluctuations in speed [3]. These pacing analyses were limited by electronic timing systems which use indiscriminate distances between checkpoints. Therefore, the aim of this study was to determine the pacing strategies and relative importance of uphill, downhill and level running for ultra-trail marathon performance in top 10 (TOP-10) runners and non-top 10 (NOT TOP-10) runners in a 100 km ultra-trail marathon. METHODS: Fifty male finishers (TOP-10: n = 6, NOT TOP-10, n = 44) and forty-six individual segments (1.5 ± 1.2 km) were analysed based on 2021 100 km UTCT STRAVA data. Twenty-three uphill (net gradient > 1.0%), 16 downhill (net gradient <-1.0%) and 7 level (net gradient between +1.0% - -1.0%) were analysed. Individual segment speeds, normalised to average race pace (segmentrel), and CV% were used to identify pacing strategies. Mann Whitney-U tests were used to compare TOP-10 and NOT TOP-10 finishers. Spearman Rank correlations were used to measure the association between overall race performance and uphill, downhill, and level running performance. Significance was set at p< 0.05). CONCLUSION: Uphill running performance remains a valuable measure of overall trail running performance as it represents a higher percentage of overall running demand. Sport scientists and laboratory technicians should continue to use uphill exercise tests to determine variation in ultra-trail marathon performance [4]. TOP-10 runners have diminished decay in initial running speed than NOT TOP-10 runners, despite a generally high variation in pace and net positive split in ultra-trail running. Neuromuscular fatigue [5] may contribute to the disparity in segmentrel between TOP-10 and NOT TOP-10 runners during the latter phases of an ultra-trail marathon.